Exploring and consolidating the brand personality elements of the political leader. Issue 3 (21st November 2018) - Jain, Varsha; Chawla, Meetu; Ganesh, B.E.; Pich, Christopher
Abstract : Purpose: This study aims to examine brand personality and its application to political branding. This study focuses on the brand personality of a political leader from the BJP Party brand (Bharatiya Janta Party). The development of a strong political brand personality is crucial for success at the polls. Little research has been dedicated to this phenomenon particularly beyond Western political and post-election contexts. Design/methodology/approach: The scope and development of the study required a qualitative approach. The theoretical frameworks of the study acted as the deductive base of the study. The insights of the respondents were the inductive base of the study. Semi-structured interviews were conducted with external stakeholders [voters]. In addition, semi-structured interviews were also adopted to capture the branding activities used by internal stakeholders [BJP]. Findings: The brand personality dimensions such as sincerity; agreeableness, competence, energy, openness, conscientiousness and emotional stability were clearly associated with a political leader. Negative qualities such as dictatorial attitudes and arrogance affected the political leader's brand personality. Religious partisanship was another strong negative trait affecting the brand personality of the political leader. Originality/value: The study has an actionable framework for political brand personality in the post-election context. It offers negative qualities to be avoided in the development of the political brand personality of the leader. It offers insights about the political brand personality of the leader in terms of young digitally savvy voters. Abstract : Propósito: Este trabajo examina la aplicación de la personalidad de marca al ámbito del marketing político y de la marca personal política. Concretamente se centra en la personalidad de marca de un líder político del partido Bharantiya Janta Party (BJP). El desarrollo de una fuerte marca personal política es crucial para el éxito en las elecciones. Pocos trabajos se han centrado hasta el momento en este fenómeno más allá del contexto político occidental. Diseño/metodología/enfoque: El alcance y desarrollo del estudio requirió la adopción de un enfoque cualitativo. El marco teórico sirvió de base deductiva al tiempo que las entrevistas realizadas sirvieron de base inductiva. Estas entrevistas fueron semi-estructuradas y dirigidas a grupos de interés externos del BJP (los votantes). Además, se realizaron entrevistas también semi-estructuradas para capturar las actividades de marca desarrolladas por los grupos de interés internos (candidatos, políticos, trabajadores y gerentes del partido). Resultados: Las dimensiones de personalidad de marca sinceridad, competencia, energía, estabilidad emocional, franqueza y escrupulosidad están claramente asociadas con un líder político. Por el contrario, rasgos negativos como las actitudes arrogantes y dictatoriales dañan la personalidad de marca de dicho líder, pero sobretodo el partidismo religioso. Originalidad/valor: El trabajo proporciona un marco de acción para la marca personal política en un contexto post-electoral. Proporciona indicaciones de los rasgos y cualidades negativas que deben de evitarse en el desarrollo de una marca personal para un líder político. Ofrece también evidencias sobre la personalidad de marca que tiene que desarrollar un líder de cara a los votantes más dinámicos y digitales.